Global distribution of ustiloxins in rice and their male-biased hepatotoxicity. (15th May 2022) - Sun, Qian; Liu, Hao; Zhang, Yongkang; Yi, Xun'e; Kong, Ren; Cheng, Shiyang; Man, Jianguo; Zheng, Lu; Huang, Junbin; Su, Guanyong; Letcher, Robert J.; Giesy, John P.; et al.
Abstract: Ustiloxins, a group of bioactive metabolites produced by the pathogen of rice false smut (RFS), have emerged as ubiquitous contaminants in RFS-occurred paddy fields and could accumulate in rice. Nevertheless, the prevalence of ustiloxins in rice and exposure risks of humans are limited. In this study, concentrations of ustiloxin A (UA) and ustiloxins B (UB), which are two predominant ustiloxins, were measured in 240 rice samples from China and 72 rice samples from 12 other counties. The detection rates (DRs) of UA and UB were 82.1% and 49.3%, respectively, and their concentrations in rice ranged from below detection limit (LOD: 0.22 μg/kg) to 85.96 μg/kg dw. Furthermore, for the first time, we reported the occurrence of UA (DR = 22.8%) in urine collected from residues of Enshi city, China. Urinary UA were significantly correlated with the activities of alanine aminotransferase in male, and this male-biased hepatotoxicity was further confirmed in mice exposure experiment. This study for the first time reported the widespread geographical distribution of ustiloxins in rice, as well as emphasized the occurrence of internal exposure and potential health risk in humans. Graphical abstract: Image 1 Highlights: Ustiloxin contamination in polished rice was ubiquitous globally. Occurrence of UA in human urine was observed with detection ratio of 22.8%. Urinary UA level was significantly correlated with ALT activity in male. Male-biased hepatotoxicity of UA was confirmed in mice.